A review on industrialised building system issues in Malaysia - Ayeop Abdul Khalil, Farah Deba; Abd. Aziz, Farah Nora Aznieta; Hassim, Salihuddin; Jaafar, Mohd Saleh (EDP Sciences, 2015)
Industrialised Building System (IBS) has been identified as a potential method to improve overall construction performance in term of quality, cost effectiveness, safety and health, waste reduction and productivity. There are several issues in managing IBS construction projects which lead to delays, poor qualities and cost overrun. This paper aims to analyze the issues in managing the construction phases of IBS projects. Based on this review, it shows that less effective use of IBS in Malaysia construction industry is due to unwillingness of the players to change from conventional system because they are not convinced with the IBS system. Therefore, appropriate bodies should help to increase the contractor’s understanding and prepareness in using IBS system in the construction industry.